Educação e cultura: discutindo a interculturalidade no contexto brasileiro e bissau-guineense - Insali, Osniel Paulo (2023)
This dissertation, entitled Discussing interculturality in the Brazilian and Bissau-Guinean contexts, sought to discuss the issue of interculturality in the Brazilian and Bissau-Guinean contexts, specifically, in their educational systems, based on the bibliographic production and the laws that support it, in each context. In the Brazilian context, the discussion was directed to laws 10.639/03 and 11.645/08 due to our assumption that these laws express the ideal defended by the intercultural approach, although the mere existence of laws does not guarantee the practice of interculturality. As Akkari (2016) argues, the intercultural approach in Brazil is mediated in two ways, namely: the first one, by the mandatory teaching of African, Afro-Brazilian and Indigenous history and culture in the official Brazilian basic education curricula; the second one, by the racial quota policies in universities. Thus, we chose the first form of mediation as an initiative aimed at interculturality in the Brazilian educational system. In the Bissau-Guinean context, different from the Brazilian context because there is no law sanctioned for this purpose, i.e., to make the teaching of Bissau-Guinean history and culture compulsory, we directed our analysis to the documents that regulate Bissau-Guinean education, i.e., the Basic Law on Education (2011) and the National Action Plan (2003) analyse the presence ofthe intercultural approach. We adopted the quanti-quali approach in the function of our research proposal. Since this is a theoretical work, it has been divided in two stages: in the first stage, bibliographies that theoretically explore the concepts we propose to discuss were analysed: culture, education, interculturality, social formation, identity and diversity. Then, the second moment was destined for the quantitative and qualitative analysis of the ideas, information and data collected through exhaustive search in three data platforms (Academic Google; Digital Library of Theses and Dissertations; and Capes Periodicals Portal). There fore, the results point to different visions, looks, understandings and questions on interculturality in the Brazilian context. While in the Bissau-Guinean context, we observe thatthe presence of this approach is too insignificant compared to the Brazilian reality.